PENGARUH LITERASI EKONOMI DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF - Abdur Rohman (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Abstract This means that students majoring in economics have a good level of economic literacy. This study aims to determine the effect of economic literacy and lifestyle on the consumptive behavior of students majoring in Islamic economics at FEBI UIN STS Jambi batch 2018. In this study, quantitative methods were used, and the data analysis methods used were instrument test, classical assumption test, and hypothesis testing. The sample in this study amounted to 74 students calculated using the Slovin formula and the data obtained through the distribution of questionnaires using a Likert scale. The results of this study indicate that Economic Literacy (X1) does not have a positive effect on Consumptive Behavior (Y). This can be seen from the t-count value of 0.917, which is smaller than the t-table of 1.667 with a significance value of 0.362, which is greater than 0.05. Lifestyle (X2) has a positive effect on consumptive behavior (Y). It can be seen from the nose t value of 4.224, which is greater than the t table of 1.667 and the significance value of 0.000 is less than 0.05. Economic literacy (X1) and Lifestyle (X2) have a joint effect on Consumptive Behavior (Y) can be seen from the calculated F value of 8.939 which is greater than F table which is 3.12 and the significance value is 0.000 less than 0.05 . while the results of the calculation of the Coefficient of Determination are 0.201 or 20.1%, meaning that the Economic Literacy variable (X1) and the Lifestyle variable (X2) have a significant effect on the Consumptive Behavior of the Students of the Islamic Economics Study Program, Sulthan Thaha Syaifuddin Jambi State Islamic University, Class of 2018 with a level of influence of 20.1%.